Renewable energy certificates trading in India: A decade in review - Aparna Sawhney (Asian Development Bank Institute (ADBI), 2022)
India has witnessed significant transformation in the energy mix over the last decade, with renewables accounting for 24% of the installed grid capacity and 10% of the electricity generation today. The achievements, however, fall short in the trajectory towards the ambitious targets set for the years 2022 and 2030. The policy package for renewables included a market-based instrument of tradeable renewable energy certificates (RECs), launched in 2010-11, which provided a channel for an alternative valuation of the green attribute of electricity generation in the country. It also provided for spatial flexibility in green power generation in resource-rich areas and compliance with the renewable portfolio obligation through REC purchase by states with shortfalls. This paper analyzes the REC market experience over the last decade and examines the implications of the changes in the trading rules over the years. It highlights that although initially the renewable certification rate rose sharply from 2% in 2011-12 to 15% in 2014-15, it subsequently dropped to 6% during 2017-19 as REC market prices plummeted and the inventory of unsold RECs accumulated. It concludes that problems of target underachievement and noncompliance of state renewable purchase obligations need to be tackled through deep reforms in the functioning of power distribution companies and not the REC mechanism per se.
Keywords: Q42; Q48; 330; India; renewable energy certificates; renewable portfolio obligation